Debt Management: Some Reflections Based on Argentina - Miguel A. Kiguel (Inter-American Development Bank, Office of the Chief Economist, 1997)
A good liability management strategy is one that helps minimize the cost of borrowing over the medium and long term. The objective is not to save the last basis point in each transaction, but rather to bring down the overall borrowing cost. This paper uses Argentina`s experience to illustrate some important elements in the design of a liability management strategy. It takes into account the specific characteristics of the Argentine capital market and of the debt instruments that are available.
Keywords: 330; Schuldenmanagement; Argentinien